2015
DOI: 10.3109/13697137.2015.1052393
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin in aging women

Abstract: Melatonin is a neurohormone secreted mainly by the pineal gland that controls circadian rhythm, which is primarily regulated by light. Although melatonin levels are known to be altered in individuals with sleep disorders, melatonin also has modulatory effects on other body systems, including the skeletal and immune systems. In addition, melatonin has been shown to interfere with carbohydrate and lipid metabolism and to have significant antioxidant effects, both directly and via its metabolites. Melatonin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 66 publications
1
20
0
5
Order By: Relevance
“…Circulating melatonin levels decline with age [28,29]. Plasma levels of melatonin are higher at nighttime throughout the life span, although it is the absolute concentrations that decline with age [30,31]. It has been shown that when melatonin is given, it provides neuroprotection [32,33] and improved cognitive function [34].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating melatonin levels decline with age [28,29]. Plasma levels of melatonin are higher at nighttime throughout the life span, although it is the absolute concentrations that decline with age [30,31]. It has been shown that when melatonin is given, it provides neuroprotection [32,33] and improved cognitive function [34].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with numerous previous studies on the use of pharmacological melatonin in the treatment of sleep disturbances in elderly men and women [cf. (110)].…”
Section: Melatonin In Reproductive Agingmentioning
confidence: 99%
“…Furthermore, lower levels of melatonin in postmenopausal women may correlate with depressive symptoms [46]. Thus, melatonin therapy may have a favorable effect on those and related symptoms, such as VMS [47].…”
Section: Circadian Rhythm Disordersmentioning
confidence: 99%